Optimalisasi TPACK Melalui Insersi Video Pembelajaran Berbasis Pendidikan Anti Korupsi Pada Mata Pelajaran Sosiologi - Bagas Narendra Parahita; Khresna Bayu Sangka; Okta Hadi Nurcahyono; Lies Nurhaini; Estetika Mutiaranisa Kurniawati; Dian Perwitasari; An Nurrahmawati; Agung Nur Probohudono; Saktiana Rizki Endiramurti (FKIP Universitas Sebelas Maret, 2022)
A teacher's ability to adapt to technology is tested when there is a significant change from face-to-face to distance learning. The most important thing is the teacher's effort to direct the attitudes and skills of students during online learning. The Technology, Pedagogy, Content Knowledge (TPACK) approach can be a solution to provide opportunities for educators to synergize anti-corruption education in learning practices. In this activity, anti-corruption education in sociology subjects was carried out using the TPACK framework approach. The service's target is the lecturers of sociology subjects in Surakarta. The method of implementing this service consists of several activities, including focus group discussion (FGD) offline to observe community needs. Then proceed with an online meeting through a zoom meeting to deliver general anti-corruption education materials and training asynchronously through the google classroom platform for 32 lessons for the benefit of training in anti-corruption education content analysis and anti-corruption learning model innovation. The preparation of anti-corruption education-based learning videos is carried out. The results of the activities were an increase in the ability of teachers to design anti-corruption learning innovations in sociology subjects and an increase in the ability of teachers to compile sociology learning videos by strengthening content knowledge of anti-corruption education insertions.